Kesopanan Dalam Email Mahasiswa Kepada Dosen - Khatimah, Khusnul; Safii, M.; Liyana, Cut Irna; Mualafina, Rawinda Fitrotul (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to analyze the politeness strategies employed by students in emails sent to lecturers, particularly in the context of submitting assignments. The research focuses on identifying the structure of the emails and the types of politeness strategies, both positive and negative, reflected in these formal communications. The data consists of a collection of student emails analyzed using a mixed-method approach (quantitative and qualitative). The analysis examines the email structure, including the opening, body, and closing sections, as well as politeness strategies based on Brown and Levinson's framework (1987). The findings reveal that students often use positive politeness strategies through expressions of gratitude and respectful markers, including polite salutations and culturally specific honorifics such as terms of respect in Bima language. Negative politeness is also observed through the use of apologies and permission-seeking to show respect and maintain good relations with lecturers. However, some students neglect essential elements of email structure, such as opening salutations or closings, with some emails consisting solely of attachments without any accompanying text. These findings highlight the need to enhance students' formal communication skills, particularly in academic contexts, to ensure appropriate politeness in professional interactions.